Education on The Chemotherapy Side Effects Management and The Use of PPE in Chemotherapy Patients Families (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Cancer is a non-communicable disease that causes the highest death after stroke and hypertension. One of the medical interventions for cancer is chemotherapy. Chemotherapy has certain side effects. However, the level of knowledge of families as patient companions about chemotherapy side effects, infection management, and use of PPE is still lacking. While in fact, a good level of knowledge can reduce anxiety in cancer patients undergoing chemotherapy. Health education and this study aim to strengthen family knowledge of chemotherapy and the use of PPE. The activity was carried out by involving 28 family members of chemotherapy patients. The results show that the majority of participants (56%) can answer the questions correctly. However, it needs to be maintained and enhanced by carrying out similar educational activities in a structured and sustainable way to increase patient and family knowledge and carry out health improvement programs, health education, for example. In addition, institutions also play a significant role in increasing the provision of health education, not only in general terms related to health but also in overcoming problems or side effects of implementing actions to become a source of information for health service facilities.